COMPLIANCE WITH RECOMMENDED PRODUCTION PRACTICES AMONG CASSAVA FARMERS IN EPE LOCAL GOVERNMENT AREA OF LAGOS STATE, NIGERIA - Ojedokun, A. O.; Kareem, D. A.; Adelana, O. I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study was carried out to investigate the factors influencing compliance with recommended production practices among cassava farmers in Epe Local Government Area of Lagos State, Nigeria. A multistage sampling procedure was used to collect data from 107 cassava farmers. Data were analyzed using descriptive statistics such as percentage, mean and standard deviation, and inferential statistics such as compliance index, and probit regression model. The study revealed that the mean age, household size, years of education, years of cassava farming experience and farm size were approximately 48 years, 6 people, 9 years, 14 years and 3 acres, respectively. The findings also revealed that almost all (98.9%) cassava farmers complied with intercropping cassava with maize or cowpea, while majority (72.0% and 58.1%) complied with the use of improved variety of cassava and planting population density of 10,000 per hectare. The results similarly revealed that majority (64.5%) of the cassava farmers fully complied with the recommended production practices. The study also showed that sex (P<0.01), years of formal education (P<0.05), primary occupation (P<0.10), and visitation by extension agent (P<0.10) were the factors that significantly influenced their full compliance with the recommended production practices. The study concluded that majority of the cassava farmers complied with recommended production practices and their compliance was influenced by sex, years of formal education, primary occupation and extension visit. The study therefore recommended that female cassava farmers should be motivated and encouraged to obtain information that will boost their output, and be enlightened on the importance of education to their farming activities.